2021
DOI: 10.1021/acs.joc.1c00497
|View full text |Cite
|
Sign up to set email alerts
|

Direct Correlation between Donor–Acceptor Distance and Temperature Dependence of Kinetic Isotope Effects in Hydride-Tunneling Reactions of NADH/NAD+ Analogues

Abstract: Recent study of structural effects on primary kinetic isotope effects (1° KIEs) of H-transfer reactions in enzymes and solution revealed that a more rigid reaction system gave rise to a weaker temperature dependence of 1° KIEs, i.e., a smaller isotopic activation energy difference (ΔE a = E aD – E aH). This has been explained within the contemporary vibrationally assisted activated H-tunneling (VA-AHT) model in which rigidity is defined according to the density of donor–acceptor distance (DADTRS) populations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 58 publications
2
13
0
Order By: Relevance
“…We have reported the structural effects on the T -dependence of KIEs of several hydride-transfer reactions of NADH/NAD + analogues in solution. We found that a smaller Δ E a accompanies a more reactive donor/acceptor that forms stronger charge-transfer (CT) complexations. , We also found that in some of the systems, the more crowded reaction centers did appear to correspond with a smaller Δ E a . , These results support our hypothesis. In these studies, the short tunneling DADs would be mainly sampled by the CT complexation thermal vibrations.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…We have reported the structural effects on the T -dependence of KIEs of several hydride-transfer reactions of NADH/NAD + analogues in solution. We found that a smaller Δ E a accompanies a more reactive donor/acceptor that forms stronger charge-transfer (CT) complexations. , We also found that in some of the systems, the more crowded reaction centers did appear to correspond with a smaller Δ E a . , These results support our hypothesis. In these studies, the short tunneling DADs would be mainly sampled by the CT complexation thermal vibrations.…”
Section: Introductionsupporting
confidence: 76%
“…27 We have attempted to use the 1,3-N,N-2CH 3 / 2CD 3 γ-2°KIEs on DMPBIH for its hydride transfer to 9-(para-substituted)phenylxanthylium ions to obtain the substituent effect on DAD TRS 's. 46,47 Here in this study, we were able to determine the N-CH 3 /CD 3 2°KIEs on both DMPBIH and MA + to evaluate the electronic structure and the rigidity order of the TRSs of their reactions in acetonitrile vs chloroform. For the reaction of HEH, however, no such 2°K IE on HEH is available.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently developed a method to compute the degenerate [D–H A] ‡ and [D H–A] ‡ structures for the TRS structures. 46 In our method, we use the classical transition state (TS) structure to construct the initial guess of the TRS structure. The dihedral angles with respect to the reaction centers at D and A in [D–H A] ‡ at a selected DAD TRS are scanned to form the 2-dimentional potential energy surface (2D-PES) for reactant state and the same is done for the [D H–A] ‡ product state structure.…”
Section: Computation Methodsmentioning
confidence: 99%
“…44 We have used the electronic, steric, and solvent effects to control the system rigidity for the study and have found that the hypothesis appears to be supported. 44–47…”
Section: Introductionmentioning
confidence: 99%